1982
DOI: 10.1007/bf00253738
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin levels, immunodeficiency and HLA in Type 1 (insulin-dependent) diabetes mellitus

Abstract: In 129 patients with Type 1 (insulin-dependent) diabetes mellitus, 100 healthy control subjects and 91 non-diabetic first degree relatives of Type 1 patients, we investigated variation in serum IgA, IgG and IgM concentrations with sex and HLA-B phenotype. Two patients with onset before the age of 15 years were completely IgA-deficient. One additional patient was completely IgG-deficient. Excluding these three cases, diabetic patients had serum IgA and IgM concentrations comparable to control subjects. IgG leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 18 publications
6
36
0
Order By: Relevance
“…The male to female ration was 4.4:1. Our study were supported by the study of Patel JC & Tripathy et al 13,14 . The high incidence of disease in male is possibly due to the fact that in most countries young men usually have more social & labor activities than women, thus favoring the Transmission of diseases.…”
Section: Discussionsupporting
confidence: 83%
“…The male to female ration was 4.4:1. Our study were supported by the study of Patel JC & Tripathy et al 13,14 . The high incidence of disease in male is possibly due to the fact that in most countries young men usually have more social & labor activities than women, thus favoring the Transmission of diseases.…”
Section: Discussionsupporting
confidence: 83%
“…Studies on immunoglobulin levels in diabetic children evaluated at different duration of disease have shown rather conflicting results [9,11,13,26]. KanakoudiTsakalidis et al [12] found transient hypogammaglobulinaemia in the early stages of juvenile diabetes.…”
Section: Discussionmentioning
confidence: 96%
“…IgG subclass deficiency has been also noted in connection with auto-immune diseases such as systemic lupus erythematous, and auto-immune cytopenias [4, 191 . Much evidence suggests that insulin-dependent diabetes mellitus (IDDM) is an auto-immune disease [2,7,8,10]. Conflicting abnormalities in immunoglobulin levels have been described in IDDM [9,11,12]. Follow up studies of Ig concentrations showed low levels of IgG, IgA, IgM at disease onset followed by a gradual normalization [12].…”
Section: Offprint Requests To: L Cortonamentioning
confidence: 97%
“…This observed frequency, however, did not significantly differ from that of the pediatric control population. In the second study [60], 2 of 129 diabetic pa tients (1.6%) had selective IgA deficiency; both patients were less than 15 years old. In the third study [61], 1 of 261 adult patients evaluated (0.4%) had IgA deficiency.…”
Section: Organ-specific Autoimmune Diseasesmentioning
confidence: 99%